2015
DOI: 10.1016/j.msard.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Eye and hand motor interactions with the Symbol Digit Modalities Test in early multiple sclerosis

Abstract: RRMS patients have an increased SI time compared to controls. Cognitive tests results, exemplified by the wSDMT, may be confounded by eye and hand motor function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 30 publications
(32 reference statements)
0
20
0
Order By: Relevance
“…Future studies should seek to disentangle the impact of motor function impairments, such as eye movements, dysarthria, and upper limbs in the performance of IPS tasks. Previous research has shown that eye movements (Nygaard et al, 2015) or dysarthria (Arnett, Smith, Barwick, Benedict, & Ahlstrom, 2008) are associated with poor performance on cognitive tests; however, more studies are needed across realms of cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should seek to disentangle the impact of motor function impairments, such as eye movements, dysarthria, and upper limbs in the performance of IPS tasks. Previous research has shown that eye movements (Nygaard et al, 2015) or dysarthria (Arnett, Smith, Barwick, Benedict, & Ahlstrom, 2008) are associated with poor performance on cognitive tests; however, more studies are needed across realms of cognition.…”
Section: Discussionmentioning
confidence: 99%
“…We tested cognitive functions using two standard tests; 1) the Montreal cognitive assessment (MoCA), 21 and 2) the symbol-digit modalities test (SDMT). 22 The MoCA was originally developed to screen for mild cognitive impairment in a geriatric outpatient population with an impairment threshold of <26. 21 An alternative threshold of <23 was determined in a larger, more heterogeneous population 23 ; we reported results based on both thresholds.…”
Section: Methodsmentioning
confidence: 99%
“…Correlation between the SDMT and PASAT has previously been reported in several studies (Brochet et al., ; Drake et al., ; Lopez‐Gongora, Querol, & Escartin, ; Nygaard et al., ). The highest correlation coefficient between the cognitive tests and the SF‐36 and the MCS was observed for the SDMT.…”
Section: Discussionmentioning
confidence: 99%
“…The oral administration is recommended when testing MS patients to minimize confounding due to upper extremity weakness or ataxia (Benedict et al, 2002). A recent study did, indeed, report a correlation between the written SDMT and the 9HPT (Nygaard et al, 2015). Some authors have, however, found that speech is slow in MS patients, which could contribute to results when using neuropsychological tests such as both the oral SDMT and the PASAT that require rapid spoken response (Arnett, Smith, Barwick, Benedict, & Ahlstrom, 2008).…”
Section: Discussionmentioning
confidence: 99%